Two Faces of Neutrophils in Liver Disease Development and Progression. Issue 1 (18th June 2021) - Cho, Yeonhee; Szabo, Gyongyi
Abstract : Neutrophils, the most abundant type of leukocyte in human blood, play a major role in host defense against invading pathogens and in sterile injury. Neutrophil infiltration is characteristic of inflammation because of its antimicrobial and cytotoxic activities. Neutrophils also actively participate in the resolution of inflammation and subsequent tissue repair by acting as a critical mediator between the inflammation and resolution phases of tissue damage. However, neutrophils that are consistently exposed to inflammatory conditions lose their self‐resolving capabilities and maintain an inflammatory phenotype, further exacerbating tissue damage. The current review describes how neutrophils interact with tissue microenvironments and acquire disease‐specific phenotypes under chronic inflammatory conditions. Here, we aim to provide a better understanding of neutrophil‐mediated pathogenesis of various liver diseases.